Teprenone for the prevention of low-dose aspirin-induced gastric mucosal injury in Helicobacter pylori-negative patients. (3rd October 2019) - Chitapanarux, Taned; Lertprasertsuke, Nirush; Kongnak, Acharaporn
Abstract: Objectives: Low-dose aspirin is the standard treatment for the prevention of cardiovascular events in at-risk patients. We performed a randomized, placebo-controlled study to determine the efficacy of teprenone for primary prevention of gastrointestinal injury in patients taking LDA for vascular protection. Methods: Patients were eligible for enrollment if they required aspirin 100 mg/day. Aspirin- naïve patients without gastroduodenal ulcer and Helicobacter pylori infection were randomized to receive teprenone 150 mg/day or placebo for 12 weeks. Primary outcome was assessed by the incidence rate of gastroduodenal ulcer. Secondary outcomes were assessed by the incidence rate of gastric mucosal injury, the improvement in modified Lanza score (MLS), gastrointestinal symptom rating scale (GSRS) and the change of gastric immunohistochemical expression for COX-1. Results: Total of 130 patients were randomized, 64 in teprenone group and 66 in placebo group. There was no incidence of ulcer after 12 weeks in both groups. Incidence of gastric mucosal injury was higher in placebo group than in teprenone group (40.0 vs. 13.38%, p = .039). Mean change of MLS was higher in placebo group than in teprenone group (0.767 ± 0.467 vs. 0.271 ± 0.158, p = .003). Scores of mucosal edema, hyperemia and hemorrhage and the change of GSRS were not different between the two groups. Change of COX-1 immunoreactive score was higher in placebo group than in teprenone group (2.433 ± 1.476 vs. 1.233 ± 0.955, p = .001). There were no treatment-related adverse events. Conclusions: Teprenone is effective in preventing gastric mucosal injury in patients taking LDA. Preventive effects of teprenone on LDA-related gastroduodenal ulcers require further investigation.